Farmer Share and Efficiency of Breeding Cow Marketing Channels in Bali - Ni Made Ayu Gemuh Rasa Astiti; I G. A. D. S. Rejeki; Marselina Ngongo (Universitas Bengkulu, 2022)
Experts have widely carried out research on cattle since 1960. However, regarding the efficiency of the cattle marketing channel in Bali, especially in the livestock group in the village of Ayunan, it is necessary to study its efficiency for that researcher conducted research to know the efficiency of marketing cattle in Bali. Using the census method, 40 farmers consisted of two livestock groups, namely the Karang Ayu livestock group and the Karya livestock group, each consisting of 20 people. Instruments or measuring tools used in the interview guide to help obtain answers from respondents are structured and closed questionnaires for open-ended questions. The results showed four channels formed from the marketing system of cattle breeds in Bali, namely marketing channel i. Breeders sell livestock to other farmers in one village (12.5%), Marketing Channel ii. Breeders sell directly to animal markets (7.5%). %), Channel iii Farmers sell livestock to blank in the cattle barn (74.5%), and IV Farmers sell livestock to blank in the animal market (5.5%). With marketing efficiency for male seeds for each channel of 0; 2.57; 1.18, and 1.61, while the marketing efficiency in each channel for female cattle is: 0;3.53; 1.50, and 1.92. It is said that the most effective marketing channel for cattle breeds in Bali is through my marketing, namely the breeders selling the cow breeds in the stables and those who buy them around the farm because they do not incur marketing costs.